Pinning of domain walls in thin ferromagnetic films - Jeudy, V. (2018)
We present a quantitative investigation of magnetic domain-wall pinning in thin magnets with perpendicular anisotropy. A self-consistent description exploiting the universal features of the depinning and thermally activated subthreshold creep regimes observed in the field-driven domain-wall velocity is used to determine the effective pinning parameters controlling the domain-wall dynamics: The effective height of pinning barriers, the depinning threshold, and the velocity at depinning. Within this framework, the analysis of results published in the literature allows for a quantitative comparison of pinning properties for a set of magnetic materials in a wide temperature range. On the basis of scaling arguments, the microscopic parameters controlling the pinning: The correlation length of pinning, the collectively pinned domain-wall length (Larkin length), and the strength of pinning disorder are estimated from the effective pinning and the micromagnetic parameters. The analysis of thermal effects reveals a crossover between different pinning length scales and strengths at low reduced temperatures.